2017
DOI: 10.1007/s40368-017-0298-4
|View full text |Cite|
|
Sign up to set email alerts
|

Variation in caries treatment proposals among dentists in Norway: the best interest of the child

Abstract: Use of BMT and sedation is related to region of education and years of experience. Awareness of ethical principles with the child´s best interest in mind, should receive increased attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Some researchers have found a more-conservative approach towards prevention and treatment of dental caries among female dentists [23][24][25][26] . In contrast, other studies have found no statistically significant relationship between dentist gender and choices for caries prevention or treatment [27][28][29] . A previous Brazilian study has also found no association between dentists' gender and decision making for restoring dental caries as seen in radiographs 30 .…”
Section: Discussionmentioning
confidence: 80%
“…Some researchers have found a more-conservative approach towards prevention and treatment of dental caries among female dentists [23][24][25][26] . In contrast, other studies have found no statistically significant relationship between dentist gender and choices for caries prevention or treatment [27][28][29] . A previous Brazilian study has also found no association between dentists' gender and decision making for restoring dental caries as seen in radiographs 30 .…”
Section: Discussionmentioning
confidence: 80%
“…This might imply that some of the self-reported restraint situations during dental treatment have occurred outside the Norwegian PDS. Rønneberg et al discussed how dentists’ educational backgrounds might influence the prevalence and acceptance of the use of restraint (Rønneberg et al 2017 ). Thus, this finding might indicate that dentists should be especially aware of patients with unknown dental history regarding behavioural objectives.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a qualitative study of Norwegian non-specialist dentists indicated that the use of restraint often is legitimised when applied in combination with conscious sedation (Aarvik et al 2021 ). In 2017, Rønneberg et al reported that 12% of dentists in the Norwegian PDS used restraint to administer acute dental treatment to young children (Rønneberg et al 2017 ). Furthermore, 50% would give a new appointment with conscious sedation.…”
Section: Discussionmentioning
confidence: 99%
“…This alarming data on dental caries and its non-treatment may reveal that low priority is given to children under 6 years of age and the failures in the primary and secondary preventive measures [10]. Also, it should be emphasized that the treatment is technically challenging, and is often dictated by the extent of the lesions, child behavior [11] and the costs for patients/reimbursement system for dentists [12]. The high prevalence of the disease, added to its impact at both individual and collective levels, the possibility of prevention and treatment performed ECC a public health problem [13].…”
Section: Introductionmentioning
confidence: 99%
“…The decision to treat the ECC should be based on individual (such as risk assessment) and family (e.g., compliance of the patient's caregiver's willingness to change behaviors that affect oral health) [12,14], as well as the professional's experience [11]. As an aid for the decisionmaking process, there are several published guidelines/ guidance/policies.…”
Section: Introductionmentioning
confidence: 99%